LUKE’S ORIGINAL VISION ON TRANSFIGURATION STORY (LUKE 9: 27-36) - VARGA, Cătălin (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
Our study is trying to identify the main instruction of the Transfiguration story, reflecting St. Luke’s point of view, using both patristic opinions and helpful modern commentaries. Apostle Luke depicts an original version of the Transfiguration Mountain: eight days passed after the promise of seeing the Kingdom of God; the transfiguration of Christ happens while He was praying; the noun ἔξοδον points out Lucanic original vision etc. The foremost kerygma that the disciples are about to learn is that of their own personal transfiguration, the only path of rediscovering the lost Image of a liturgical membership. The presence of the most towering prophets of the Old Testament here on the mountain, certify that before you enter into the Kingdom of God, you have to cross the Golgotha scene, a journey that all of us have to take in order to inherit eternal life. Trying to achieve a proper exegesis of the Sacred Texts is not easy to reach, that is why our work is far from being accomplished.